Nudging farmers in crop choice using price information: Evidence from Ethiopian Commodity Exchange - Dagim G. Belay; Hailemariam Ayalew (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2019)
The lack of reference price information is often regarded as one of the most pervasive aspect of incomplete commodity markets in developing countries. Previous studies on the effects of price information emphasize the market participation and performance of rural households. This paper argues that access to reference price information influences farmers' crop choice decision, the most important decision in farming activity. The study exploits the variation in timing and spatial distance of the publicly run Ethiopian Commodity Exchange (ECX) price tickers as an indicator for variation in the intensity of access to reference price information among rural villages in Ethiopia. The paper finds that access to price information increases the average farm-gate prices for traded commodities and incentivizes farmers to allocate more land, fertilizer and improved seeds to commodities traded in the ECX. It also nudges farmers to produce more of the traded commodities, increasing the output share of ECX-traded commodities.
Keywords: D02; D83; Q02; Q12; Q13; 330; Crop choice; Commodity exchange; Price information; Ethiopia